Long-Term Outcomes of Surgery for Thymic Carcinoma: Experience of 25 Cases at a Single Institution - Tagawa, Tetsuzo; Suzuki, Hidemi; Nakajima, Takahiro; Iwata, Takekazu; Mizobuchi, Teruaki; Yoshida, Shigetoshi; Yoshino, Ichiro (The Thoracic and Cardiovascular Surgeon, 2015)
Background Thymic carcinoma, a relatively rare entity, often presents as locally advanced disease, and sometimes as distant metastatic disease. The treatment strategy, long-term surgical outcomes and clinical prognostic factors have yet to be fully elucidated.Methods Clinical charts of 25 patients who underwent surgery for thymic carcinoma at our institution from 1991 to 2014 were retrospectively reviewed.Results The Masaoka stage was stage I in three patients (12%), II in eight (32%), III in four (16%), IVa in four (16%), and IVb in six (24%). Histologic subtypes were squamous cell carcinoma in 12 patients, well-differentiated neuroendocrine carcinoma in 5, undifferentiated carcinoma in 3, adenocarcinoma in 1, and others in 4. Three patients had paraneoplastic syndrome including myasthenia gravis, multiple endocrine neoplasia type 1 (MEN1), and Cushing syndrome. Neoadjuvant chemotherapy was administered to five patients (20%). Complete resection was achieved in 17 patients (68%). There were no perioperative deaths. Twelve patients received postoperative therapy. The 5- and 10-year overall survival rates were 76.2 and 63.5%, respectively. The 5- and 10-year survival rates of patients with Masaoka stage I–III were 88.9 and 74.1%, respectively, whereas the 5-year survival rate of stage IV was 50.0%. The 5- and 10-year survival rates of 17 patients who underwent complete resection were 88.9 and 71.1%, respectively. Of the 17 patients with complete resection, 3 patients experienced recurrence including lung and supraclavicular lymph node.Conclusion Even for this highly malignant disease, surgery could contribute to favorable long-term outcomes in the setting of multimodality therapy.
Keywords: thymus; mediastinum; surgery